Federal civil service manpower statistics 1983 - Statistic Unit of the Establishments and Training Department (Lagos, Nigeria : Statistics unit, Establishment Department Office, Office of the secretary to the Federal Military Government and Head of Service, 1986)
This manual provides information on the federal civil service of Nigeria, its staff structure, size, distribution and utilization. This edition further attempts to update the data on earlier series of the publication.
nmn, 29/03/19
Loans
Keywords: Federal civil service; Federal civil service - manpower; Federal civil service - statistics; Nigeria